First report of trichospilus diatraeae (Hymenoptera: Eulophidae) parasitizing pupae of methona themisto (lepidoptera: Nymphalidae) - Do Nascimento, Diego Arcanjo [UNESP]; Dos Santos, Fábio Araújo [UNESP]; de Carvalho, Vanessa Rafaela [UNESP]; de Souza, Caroline Dias [UNESP]; Wilcken, Carlos Frederico (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2020)
Urban afforestation is a practice used in urban centers. Of the plant species used, Brunfelsia pilosa and B. uniflora are used in most cities. The main pest for B. pilosa and B. uniflora is the lepidopteran Methona themisto which can feed on the leaves of the plant and cause its death. As a solution, biological control with parasitoid insects can be an alternative to chemical means. The present study aimed to investigate if M. themisto can be parasitized by Tichospilus diatraeae. Six pupae of M. themisto were offered to T. diatraeae and exposed to parasitism for 72 hours. The observed parasitism was 66% with 90% of the emergence of adult parasitoids. The parasitoid egg-to-adult life cycle was 18 ± 1 days and an average of 510 ± 91.21 insects emerged per pupa. Each parasitoid consumed an average of 1.13 ± 0.16 mg of pupal content to compete its cycle. The results record for the first time in the literature that M. themisto may be a host of T. diatraeae and consequently applied in biological control programs of this pest.
Primer informe de trichospilus diatraeae (Hymenoptera: eulophidae) que parasita pupas de methona themisto (lepidoptera: nymphalidae)
Keywords: Biological control; Forest entomology; Insects parasitoids